Perbandingan Asam Fenolat dan Total Fenolik Kopi Arabika Bogor dari Pengolahan Pascapanen dan Tingkat Sangrai Berbeda - Muhammad Reza; Dian Herawati; Feri Kusnandar (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2023)
Coffee is rich in phenolic compounds, which can be evaluated by the total phenolic or specific individual phenolics. The composition and concentration of phenolics in coffee are affected by various factors, including postharvest and roasting. This study aimed to compare the ratio of phenolic acid (measured as chlorogenic acid) to total phenolic in Bogor arabica coffee, considering different postharvest treatments and roasting levels. The coffee samples were treated with different postharvest (dry, wet, and honey) and roasting processes (light and dark). Green coffee bean was used as a control. The roasting process involved heating the coffee at temperatures ranging from 147.9 to 178.8°C for light roasting, and 190.2 to 200°C for dark roasting (10 minutes each). The color of the coffee beans, concentration of phenolic acid in the coffee extract, and total phenolic in the coffee extract were analyzed using a colorimeter, HPLC, and spectro-photometer respectively. The results showed that roasting significantly intensified the dark color of Bogor arabica coffee. Among the phenolic acids, the 5-CQA isomer emerged as the most dominant and was also the most susceptible to degradation during roasting. As the roasting level increased, the concentration of phenolic acid consistently decreased. Interestingly, the total phenolic initially increased in light roasted coffee but decreased in dark roasted coffee. Green coffee beans exhibited the highest proportion of phenolic acid (83%), whereas dark roasted coffee had the lowest proportion (19%). Although light roasted coffee had the highest total phenolic, its phenolic acid concentration decreased significantly compared to green coffee beans.